Correlation of Diffusion Tensor Imaging Parameters in the Canine Brain. Issue 1 (February 2015) - Leong, Dalun; Calabrese, Evan; White, Leonard E; Wei, Peter; Chen, Steven; Platt, Simon R; Provenzale, James M
The goal of this study was to determine the degree to which ex vivo diffusion tensor imaging (DTI) parameters correlate to one another in white matter regions on very high resolution MR scans. Specifically, we hypothesized that radial diffusivity (RD) and apparent diffusion coefficient (ADC) would correlate more closely than either would correlate with fractional anisotropy (FA). We performed post mortem DTI imaging on three canine brains on a 7T MR scanner (TR = 100 ms, NEX = 1, gradient amplitude = 600 mT/m, b = 1492–1, 565 s/mm 2 ) and generated maps of FA, RD, and ADC. We measured RD, FA and ADC within 14 regions of interest representative of various portions of white matter. We compared the three combinations of values, i.e., FA vs ADC, FA vs RD and ADC vs RD, using linear regression models. Linear regression demonstrated that RD was significantly correlated with FA (p ≪ 0.01; R 2 = 0.3053) and also with ADC (p ≪ 0.01; R 2 = 0.6755), but to a much greater degree. However, ADC was not significantly correlated with FA (p = 0.526; R 2 = 0.101). Our findings suggest that both RD and ADC reflect similar cytoarchitectural features, most likely that of myelination, whereas FA values likely reflect both myelination and additional microstructural features that constrain the diffusion of water in white matter.